Social and political movements : readings on Punjab - Puri, Harish K.; Judge, Paramjit S. (Jaipur : Rawat Publications, 2000)
Contributed articles.
Includes bibliographical references and index.
Keywords: Social movements -- India -- Punjab -- History; Punjab (India) -- Social conditions; Punjab (India) -- Politics and government